The Effects of Violent Crime on the Socio-Economic Development in Gboko Metropolis (Global Journal of Human-Social Science, 2019)
Organizations around the world consist of people with a similar aim, objective, set goal, who work in cooperation with one another in achieving what an individual cannot be able to accomplish in isolation. The main aim of this study is to investigate the effect of interpersonal relations practices on productivity in Nigeria Social Insurance Trust Fund (NSITF), Abuja. A survey research design was adopted for this study, using a population of 197 staff of Nigeria Social Insurance Trust Fund (NSITF) Abuja from top management cadre, middle, and low cadre officers. A simple random sampling technique was used to select the sample size. The instrument for data collection was the questionnaire. Data collected was analyzed using mean, and standard deviation. Thus, chi-square was used to test the hypotheses at 0.05 Alpha level of significance. The study made the following findings: there is a major relationship between interpersonal relations and achievement of Nigeria Social Insurance Trust Fund (NSITF), Abuja, and there is a significant relationship between interpersonal relations and workers performance in Nigeria Social Insurance Trust Fund (NSITF), Abuja. The study therefore, recommends that: management staff and other senior staff in the organization should create a conducive atmosphere to facilitate good human relations and subsequently teamwork for greater or higher productivity.
Keywords: effect; interpersonal relations; practices; productivity